Early Association of Prosodic Focus with alleen ‘only’: Evidence from Eye Movements in the Visual-World Paradigm - Mulders, Iris; Szendrői, Kriszta (Frontiers in Psychology, 2016)
In three visual-world eye tracking studies, we investigated the processing of sentences containing the focus-sensitive operator alleen ‘only’ and different pitch accents, such as the Dutch Ik heb alleen SELDERIJ aan de brandweerman gegeven ‘I only gave CELERY to the fireman.’ versus Ik heb alleen selderij aan de BRANDWEERMAN gegeven. ‘I only gave celery to the FIREMAN.’. Dutch, like English, allows accent shift to express different focus possibilities. Participants judged whether these utterances match different pictures: in Experiment 1 the Early Stress utterance matched the picture, in Experiment 2 both the Early and Late Stress utterance did, and in Experiment 3 neither did. We found that eye-gaze patterns start to diverge across the conditions already as the indirect object is being heard. Our data also indicate that participants perform anticipatory eye-movements based on the presence of prosodic focus during auditory sentence processing. Our investigation is the first to report the effect of varied prosodic accent placement on different arguments in sentences with a semantic operator, alleen ‘only’, on the time course of looks in the visual world paradigm. Using an operator and auditory stimuli allowed us to confirm that prosodic focus information immediately gets integrated into the semantic processing of the proposition. Our study thus provides further evidence for fast, incremental prosodic focus processing in natural language.